2020
DOI: 10.1093/infdis/jiaa616
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Genotypes in Hospitalized Children With Acute Gastroenteritis Before and After Rotavirus Vaccine Introduction in Blantyre, Malawi, 1997–2019

Abstract: Introduction Rotavirus vaccine (Rotarix®, RV1) has reduced diarrhea-associated hospitalizations and deaths in Malawi. We examined the trends in circulating rotavirus genotypes in Malawi over a 22-year period to assess the impact of RV1 introduction on strain distribution. Methods Data on rotavirus-positive stool specimens among children age <5 years hospitalized with diarrhea in Blantyre, Malawi before (July 1997 – Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 39 publications
4
25
2
Order By: Relevance
“…Several recent studies have reported the increased proportion of G3P [8] strains, e.g., in Australia [14], Japan [32], Thailand [28], Indonesia [29], Pakistan [33], Dominican Republic [25], Brazil [34], Spain [20], Mozambique [24], Malawi [35] and Botswana [36]. The global G3 sequences available from GenBank showed extensive genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have reported the increased proportion of G3P [8] strains, e.g., in Australia [14], Japan [32], Thailand [28], Indonesia [29], Pakistan [33], Dominican Republic [25], Brazil [34], Spain [20], Mozambique [24], Malawi [35] and Botswana [36]. The global G3 sequences available from GenBank showed extensive genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Continued surveillance to monitor whether this particular strain becomes endemic in Kenya and the wider Africa continent in the face of increased RVA vaccine coverage is important to optimize RVA vaccine-mediated control. Notably, recent studies in Botswana [36], Mozambique [24], Malawi [35] and Ethiopia [37] reported increased prevalence of G3 type viruses but sequencing data from these studies are not yet available.…”
Section: Discussionmentioning
confidence: 99%
“…The dsRNA was reverse transcribed to complementary DNA (cDNA) using random primers (Invitrogen, Paisley, UK) and reverse transcriptase enzyme (Superscript III MMLV-RT, Invitrogen, Paisley, UK) [9]. The cDNA was used to assign G genotype (G1, G2, G3, G4, G8, G9, G10, G11, G12) and P genotype (P [4], P [6], P [8], P [9], P [10], P [11], P [14]) using a multiplex heminested RT-PCR as described previously [5].…”
Section: Rotavirus Detection and Genotypingmentioning
confidence: 99%
“…The most frequently detected rotavirus genotypes were G1P [8], G2P [4], G2P [6], G12P [6] and G12P [8] [5], which comprised 66.57% (636/1,050) of all genotypes (Table S3). In RV1 unvaccinated children, regardless of the genotype, most gastroenteritis episodes were classified as severe (66.67%, 424/636) and severity scores did not differ by genotype (unadjusted Kruskal-Wallis test, P=0.544).…”
Section: Relationship Between Rotavirus Genotype Gastroenteritis Severity and Vaccination With Rv1mentioning
confidence: 99%
See 1 more Smart Citation